DNA damage and oxidative stress induced by CeO2 nanoparticles in human dermal fibroblasts: Evidence of a clastogenic effect as a mechanism of genotoxicity. Issue 6 (September 2015) - Benameur, Laila; Auffan, Mélanie; Cassien, Mathieu; Liu, Wei; Culcasi, Marcel; Rahmouni, Hidayat; Stocker, Pierre; Tassistro, Virginie; Bottero, Jean-Yves; Rose, Jérôme; Botta, Alain; Pietri, Sylvia
Abstract The broad range of applications of cerium oxide (CeO2) nanoparticles (nano-CeO2) has attracted industrial interest, resulting in greater exposures to humans and environmental systems in the coming years. Their health effects and potential biological impacts need to be determined for risk assessment. The aims of this study were to gain insights into the molecular mechanisms underlying the genotoxic effects of nano-CeO2 in relation with their physicochemical properties. Primary human dermal fibroblasts were exposed to environmentally relevant doses of nano-CeO2 (mean diameter, 7 nm; dose range, 6 × 10−5–6 × 10−3 g/l corresponding to a concentration range of 0.22–22 µM) and DNA damages at the chromosome level were evaluated by genetic toxicology tests and compared to that induced in cells exposed to micro-CeO2 particles (mean diameter, 320 nm) under the same conditions. For this purpose, cytokinesis-blocked micronucleus assay in association with immunofluorescence staining of centromere protein A in micronuclei were used to distinguish between induction of structural or numerical chromosome changes (i.e. clastogenicity or aneuploidy). The results provide the first evidence of a genotoxic effect of nano-CeO2, (while not significant with micro-CeO2) by a clastogenic mechanism. The implication of oxidative mechanisms in this genotoxic effect was investigated by (i) assessing the impact of catalase, a hydrogen peroxide inhibitor, and (ii) by measuring lipid peroxidation and glutathione status and their reversal by application of N-acetylcysteine, a precusor of glutathione synthesis in cells. The data are consistent with the implication of free radical-related mechanisms in the nano-CeO2-induced clastogenic effect, that can be modulated by inhibition of cellular hydrogen peroxide release.